Status Resistensi dan Keberadaan Virus Dengue pada Nyamuk Aedes Sp di Kelurahan Pinang Kencana, Kota Tanjungpinang, Kepulauan Riau - Rinaldi Daswito; Kholilah Samosir; Mohd. Abdul Rahman; Silfy Tiffany (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2022)
Tanjungpinang Timur Village is an endemic area, and every year there is a death rate due to dengue fever. This study aimed to map the resistance and presence of the dengue virus in Aedes sp mosquitoes in Pinang Kencana Village. This research was observational with a descriptive approach. The samples were mosquitoes bred in the Vector Laboratory of Poltekkes, Ministry of Health, Tanjungpinang, from eggs trapped in ovitraps distributed in the study area. A total of 78 ovitraps were placed inside the house, 45 were positive, while 45 positive ovitraps were placed outside the house out of a total of 84 ovitraps. Ovitrap index numbers outside (57.7%) and inside the house (53.6%) with an overall ovitrap index of 55.6%. The resistance test results using the CDC bottle bioassay method showed that Aedes sp mosquitoes from Pinang Kencana Village were resistant to the pesticide deltamethrin dose of 10 g/bottle with a diagnosis time of 30 minutes with a mosquito mortality percentage of 68.33%. The PCR results for dengue virus in the sample mosquitoes showed no presence of dengue virus in the mosquito samples, both DEN-1, DEN-2, DEN-3, and DEN-4 serotypes.